Moderate-intensity exercise training or high-intensity interval training to improve aerobic fitness during exercise prehabilitation in patients planned for elective abdominal cancer surgery?. Issue 1 (January 2022) - Franssen, Ruud F.W.; Janssen-Heijnen, Maryska L.G.; Barberan-Garcia, Anael; Vogelaar, F. Jeroen; Van Meeteren, Nico L.U.; Bongers, Bart C.
Abstract: Low preoperative aerobic fitness is associated with an increased risk of postoperative complications and delayed recovery in patients with abdominal cancer. Surgical prehabilitation aims to increase aerobic fitness preoperatively to improve patient- and treatment-related outcomes. However, an optimal physical exercise training program that is effective within the short time period available for prehabilitation (<6 weeks) has not yet been established. In this comparative review, studies (n = 8) evaluating the effect of short-term (<6 weeks) moderate-intensity exercise training (MIET) or high-intensity interval training (HIIT) on objectively measured aerobic fitness were summarized. The content of exercise interventions was critically appraised regarding the frequency, intensity, time, type, volume, and – monitoring of – progression (FITT-VP) principles. Three out of four studies evaluating HIIT showed statistically significant improvements in oxygen uptake at peak exercise (VO2peak ) by more than 4.9%, the coefficient of variation for VO2peak . None of the two studies investigating short-term MIET showed statistically significant pre-post changes in VO2peak . Although short-term HIIT seems to be a promising intervention, concise description of performed exercise based on the FITT-VP principles was rather inconsistent in studies. Hence, interpretation of the results is challenging, and a translation into practical recommendations is premature. More emphasis should be given to individual responses to physical exercise training. Therefore, adequate risk assessment, personalized physical exercise training prescription using the FITT-VP principles, full reporting of physical exercise training adherence, and objective monitoring of training progression and recovery is needed to ensure for a personalized and effective physical exercise training program within a multimodal prehabilitation program.